Effect of drought stress on periods prior of weed interference (PPWI) in bean crop using arbitrary and tolerance estimation - Parreira, Mariana C. (2015)
Weeds cause big losses in the crops yields. Drought combined with high temperatures can influence and enhance this effect. The present study was designed to determine the periods prior of weed interference on bean crops subjected to conditions of hydric comfort and drought, using two distinct approaches: arbitrary level of 5% productivity loss and tolerance level. The experimental treatments consisted of five coexistence periods of the crop and weeds: 0-15, 0-30, 0-45, 0-60, 0-harvest days after emergence and a control plot that was kept weed-free throughout the study period. The experimental design was a random block design with four replications. The periods prior of weed interference were consisted of 9 and 10 days of coexistence at the arbitrary 5% productivity loss and four and nine days at tolerance level for the conditions of hydric comfort and drought, respectively. Beta maritima was the major weed interfering in bean. Drought stress reduced the bean productivity up to 63%, where weeds reduced it by 65%. The tolerance level was more sensitive to abiotic stress influence in weed-crop interference.